Az SZTE TIK látogatóinak környezeti és társadalmi felelősségvállalása: egy kérdőíves felmérés eredményei - Erdélyi, Evelyn; Bekk, Éva; Schulz, Gábor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The Brundland-report has been one of the most important milestones concerning sustainability and its practical considerations. This is especially true for companies. Friedman’s article triggered development in this issue back in 1970, leading to the highly important role of corporate social responsibility it bears today. The Learning and Information Center of the University considers it to be of utmost imporance to participate in preserving the environment and contribute to employee and visitor satisfaction. This paper intends to present some current definitions for corporate social responsibility and its implications for our institution. Afterwards, we’ll investigate into the opinions and attitudes of our students and establish the level of progression we have made so far, as seen by these stakeholders of our organization.